Respuesta :

The inverse of the function is [tex]f^{-1}(x)=\frac{x-11}{4}[/tex]

Explanation:

The given function is [tex]f(x)=4x+11[/tex]

We need to determine the inverse of the function.

Inverse of the function:

The inverse of the function can be determined by interchanging the variables x and y and then solving the function for the variable y.

Here, the function f(X) is y.

Thus, the function becomes [tex]y=4x+11[/tex]

Interchanging the variables, we get;

[tex]x=4y+11[/tex]

Now, we shall solve the expression for the variable y.

Thus, we have,

[tex]x-11=4y[/tex]

 [tex]\frac{x-11}{4}=y[/tex]

Thus, the inverse of the function is [tex]f^{-1}(x)=\frac{x-11}{4}[/tex]

Answer:

The answer is b.

Step-by-step explanation:

ACCESS MORE